Pengembangan Media Pembelajaran Terintegrasi Teknologi dan Budaya Berorientasi Pemahaman Konsep Gabungan dan Irisan Himpunan - Ulfa Lu'luilmaknun; Junaidi Junaidi; Gilang Primajati; Eka Kurniawan; Dita Oktavihari; Putri Surya (FKIP Universitas Mataram, 2026)
Students' low level of mathematical conceptual understanding remains one of the major challenges in mathematics education, leading to difficulties in solving mathematical problems accurately. One effort to address this issue is to develop learning media that integrate digital technology with local cultural contexts, thereby creating more meaningful learning experiences. This study aimed to develop an ethnomathematics-based interactive learning media that meets the criteria of validity and practicality. The study employed a Research and Development (R&D) approach using the Four-D (4D) development model, consisting of the define, design, develop, and disseminate stages. However, the research was limited to the develop stage, which involved validation by media experts and subject matter experts, as well as practicality assessment by practitioners. The research instruments included media expert validation sheets, material expert validation sheets, and practitioner response questionnaires. The data were analyzed quantitatively using descriptive statistics in the form of mean scores and feasibility percentages. The findings indicate that the developed ethnomathematics-based interactive learning media achieved valid criteria based on expert evaluations and practical criteria based on practitioners' assessments. Therefore, the developed media can serve as an alternative mathematics learning resource to support students' conceptual understanding.